Photooxidation of a twisted isoquinolinone - Li, Gang (2020)
Understanding the oxidation mechanism and positions of twistacenes and twistheteroacenes under ambient conditions is very important because such knowledge can guide us to design and synthesize novel, larger stable analogues. Herein, we demonstrated for the first time that a twisted isoquinolinone can decompose under oxygen and light at room temperature. The as‐decomposed product 1 was fully characterized through conventional methods as well as single‐crystal structure analysis. Moreover, the physical properties of the as‐obtained product were carefully investigated and the possible formation mechanism was proposed.